2008
DOI: 10.1681/asn.2007111166
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ANCA-Mediated Leukocyte-Endothelial Cell Interactions In Vivo

Abstract: Anti-myeloperoxidase (anti-MPO) antibodies have been implicated in the pathogenesis of small-vessel vasculitis, but the molecular mechanisms by which these antibodies contribute to disease are unknown. For determination of how anti-MPO antibodies affect inflammatory cell recruitment in small-vessel vasculitis, intravital microscopy was used to monitor leukocyte behavior in the accessible cremasteric microvessels under various experimental conditions. After local pretreatment of the cremaster muscle with cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 43 publications
4
58
0
Order By: Relevance
“…One day after disease induction, signs of acute inflammation are present, such as hematuria and glomerular neutrophil influx, whereas leukocyturia, albuminuria, and glomerular crescents are important disease characteristics on day 7. 9 Because the pathogenicity of anti-MPO antibodies in mice seems to be Fc␥R dependent, 11,25 we hypothesized that EndoS-mediated deglycosylation of the anti-MPO IgG Fc tail could reduce the pathogenic effects of the antibodies. Indeed, we found that EndoSmediated deglycosylation of anti-MPO IgG markedly diminished both early and late disease characteristics of this model.…”
Section: Discussionmentioning
confidence: 99%
“…One day after disease induction, signs of acute inflammation are present, such as hematuria and glomerular neutrophil influx, whereas leukocyturia, albuminuria, and glomerular crescents are important disease characteristics on day 7. 9 Because the pathogenicity of anti-MPO antibodies in mice seems to be Fc␥R dependent, 11,25 we hypothesized that EndoS-mediated deglycosylation of the anti-MPO IgG Fc tail could reduce the pathogenic effects of the antibodies. Indeed, we found that EndoSmediated deglycosylation of anti-MPO IgG markedly diminished both early and late disease characteristics of this model.…”
Section: Discussionmentioning
confidence: 99%
“…44 The synergy between TNF-a, b2-integrins, and FcgR was confirmed in vivo in experimental anti-MPO-induced AAV. 6 Complement further amplifies the proinflammatory responses of adherent neutrophils in the presence of ANCA. Neutrophil-bound ANCAs trigger the complement classic pathway exclusively on adherent neutrophils, a condition allowing access of ANCA to their antigens in plasm 45 and in synergy with the alternative pathway activated on TNFstimulated cells.…”
Section: Proinflammatory Effects Of Adhesion: Amplification By Anca Amentioning
confidence: 99%
“…Both physical trapping and immediate arrest involving adhesion molecules have been demonstrated in different models ( Figure 5). In particular, the trapping of neutrophils in microvessels ( Figure 5A) may explain the ANCA-associated accumulation of neutrophils in the glomerulus 6 ; it does not involve endothelial adhesion molecules and is reminiscent of selectinindependent neutrophil sequestrations observed in pulmonary capillaries. 72 Participation of platelets in neutrophil adhesion to the endothelium has been observed in experimental anti-GBM GN ( Figure 5B).…”
Section: Nonconventional Pathways Of Leukocyte Recruitment In Glomerulimentioning
confidence: 99%
See 1 more Smart Citation
“…MPO-ANCAs reduce leukocytes rolling over the endothelium and augment adhesion and transmigration across the endothelium. Blocking Fcϒ receptors and β2 integrins can inhibit this process (72,73).…”
Section: In Vivo and In Vitro Support Comes From Effects On Pathogenementioning
confidence: 99%